Timing of syncope in ictal asystole as a guide when considering pacemaker implantation. (19th September 2021) - van Westrhenen, Anouk; Shmuely, Sharon; Surges, Rainer; Diehl, Beate; Friedman, Daniel; Leijten, Frans S. S.; van Hoey Smith, Jorien; Benditt, David G.; van Dijk, J. Gert; Thijs, Roland D.
Abstract: Introduction: In patients with ictal asystole (IA) both cardioinhibition and vasodepression may contribute to syncopal loss of consciousness. We investigated the temporal relationship between onset of asystole and development of syncope in IA, to estimate the frequency with which pacemaker therapy, by preventing severe bradycardia, may diminish syncope risk. Methods: In this retrospective cohort study, we searched video‐EEG databases for individuals with focal seizures and IA (asystole ≥ 3 s preceded by heart rate deceleration) and assessed the durations of asystole and syncope and their temporal relationship. Syncope was evaluated using both video observations (loss of muscle tone) and EEG (generalized slowing/flattening). We assumed that asystole starting ≤3 s before syncope onset, or after syncope began, could not have been the dominant cause. Results: We identified 38 seizures with IA from 29 individuals (17 males; median age: 41 years). Syncope occurred in 22/38 seizures with IA and was more frequent in those with longer IA duration (median duration: 20 [range: 5–32] vs. 5 [range: 3–9] s; p < .001) and those with the patient seated vs. supine (79% vs. 46%; p = .049). IA onset always preceded syncope. In 20/22 seizures (91%), IA preceded syncope by >3 s. Thus, in only two instances was vasodepression rather than cardioinhibition the dominant presumptive syncope triggering mechanism. Conclusions: In IA, cardioinhibition played an important role in most seizure‐induced syncopal events, thereby favoring the potential utility of pacemaker implantation in patients with difficult to suppress IA.